The Empire of the Ptolemies - Mahaffy, J. P. 1839-1919 (Cambridge library collection. Classics, 1895)
The classical scholar J. P. Mahaffy (1839–1919) is known equally for his work on Greek texts and Egyptian papyri (his edition of The Flinders Petrie Papyri is reissued in the Cambridge Library Collection). This illustrated work of 1895 is a sort of sequel to his Alexander's Empire of 1887 (also reissued in this series), in which he focuses specifically on the dynasty of the Ptolemies, rulers of Egypt, but also, as he points out, of wider territories and subject kingdoms. The study of the successor states of Alexander was in its infancy at this period, and Mahaffy regards this work as a pioneering discussion of various problems raised by the limited literary record, hoping this will stimulate further research, in the welcome context of an increasing number of archaeological discoveries relevant to this late period in the long history of ancient Egypt